Entropy analysis of systems exhibiting negative probabilities - Machado, J. A. Tenreiro (2015)
This paper addresses the concept of negative probability and its impact upon entropy. An anal-ogy between the probability generating functions, in the scope of quasiprobability distribu-tions, and the Grünwald–Letnikov deﬁnition of fractional derivatives, is explored. Two distinct cases producing negative probabilities are formulated and their distinct meaning clariﬁed. Nu-merical calculations using the Shannon entropy characterize further the characteristics of the two limit cases.